Development Of Mangrove And Salinity Distribution Mapping For The Environmental Sustainability In Kuantan Estuary Using RS-GIS Technology - Khaled Omar, Abdullah Al-Orabi (2023)
The mangrove ecosystem is one of the most productive ecosystems on earth. Mangrove act as a habitat for various species including fish, birds, and crocodiles. However, massive development activities in the Kuantan areas have given enormous pressure to the coastal ecosystem especially mangrove. Development for residential and industrial uses, followed by aquaculture, are the primary threats to Kuantan's mangrove forest. As a result, continuous monitoring of mangroves is essential to ensure their preservation and the development of a sustainable coastal zone. The objectives of this study are to employ remote sensing and gis, to determine how mangrove distribution is affected by salinity. And to create a mangrove distribution map that illustrates the level of degradation from 2002 to 2018 as a result of development in Kuantan. This study examines the mangrove species distribution, and degradation level between 2002 and 2018. Semi-supervised classification was used to assess changes in mangrove distribution using Landsat 7 and Sentinel-2 satellite images of the Kuantan-Belat estuary. The total mangrove cover in 2018 was 1,541.9 ha, a 34% drop from the total area of 2,335.8 ha in 2002. The Kappa coefficient (K) for classification was 0.95 in 2002 and 0.92 in 2018. The diversity of mangroves was distributed in accordance with salinity in the brackish water. Thus, analytical solutions were used to replicate the estuary's longitudinal salinity distribution. The species were distributed on the three salinity zones observed on Kuantan-Belat estuary, polyhaline, mesohaline and oligohaline. Five mangroves’ species were detected dominated by Sonneratia alba and Rhizophora mucronate. This study provided a clear mapping of changes in mangrove cover over the decades to assist environmentalists, researchers, and managers in developing better policies. It also raised awareness, revive interest in mangroves, and create a database that will aid in the preservation of mangroves, as well as revealed the total area of Kuantan mangroves between 2002 and 2018.